2000
DOI: 10.1093/jn/130.4.931s
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Studies on Umami Taste

Abstract: The first electrophysiological studies on umami taste were conducted with rats and cats. Unlike humans, these animals did not show a large synergism between monosodium glutamate (MSG) and disodium guanylate (GMP) or disodium inosinate (IMP). The taste nerve responses of these animals to umami substances were not differentiated from the salt responses. The canine taste system was sensitive to umami substances and showed a large synergism between MSG and GMP or IMP. The umami substances showed no enhancing effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 12 publications
0
50
0
4
Order By: Relevance
“…In electrophysiological studies, recording from afferent chorda tympani fibers in dogs, taste cells were found that responded to GLU application to the tongue independent of sodium receptor stimulation (sodium receptors were blocked with amiloride) (Nakamura and Kurihara, 1991). In addition to these earlier results, glossopharyngeal afferent fibers were identified in mice that responded to GLU (and mononucleotide) applications to the tongue, but not to the other basic tastants (Kurihara and Kashiwayanagi, 2000).…”
Section: Physiology Of Glutamatementioning
confidence: 79%
See 1 more Smart Citation
“…In electrophysiological studies, recording from afferent chorda tympani fibers in dogs, taste cells were found that responded to GLU application to the tongue independent of sodium receptor stimulation (sodium receptors were blocked with amiloride) (Nakamura and Kurihara, 1991). In addition to these earlier results, glossopharyngeal afferent fibers were identified in mice that responded to GLU (and mononucleotide) applications to the tongue, but not to the other basic tastants (Kurihara and Kashiwayanagi, 2000).…”
Section: Physiology Of Glutamatementioning
confidence: 79%
“…The result was that the umami taste receptor is probably a metabotropic, but not an ionotropic GLU receptor, perhaps somewhat similar to, but not identical with the metabotropic GLU receptor subtype-4. Kurihara and Kashiwayanagi (2000) concluded from their human studies that the umami taste receptor may be a unique GLU receptor subtype.…”
Section: Physiology Of Glutamatementioning
confidence: 99%
“…It is known that IMP contributes to the pleasant, fresh flavor of the meat (Howgate, 2005). Furthermore, IMP acts as a flavor enhancer of meaty foods, especially L-glutamate, an umami flavor (Kurihara and Kashiwayanagi, 2000;Kawai et al, 2002;Li et al, 2002), IMP is as an important indicator to measure the meat flavor. Some studies showed that IMP heated in water and fat could produce obvious meat flavor (Heath and Reineccius, 1986).…”
Section: The Effect Of Scesc On Imp Content Of Breast and Thighmentioning
confidence: 99%
“…The omission of glutamate from synthetic extracts generally resulted not only in the expected decrease in umami taste but, in the case of the sea urchin extract, led to an increase in sweetness (Fuke & Ueda 1996). Glutamate flavour has also been shown to intensify in the presence of a very small concentration of nucleotides such as inosine 5?-monophosphate (IMP) or guanosine monophosphate (GMP) (Kurihara & Kashiwayanagi 2000;Kawai et al 2002); however, IMP or GMP concentrations were not quantified in the current study.…”
Section: Discussionmentioning
confidence: 62%